Blood pressure and heart rate and withdrawal of antihypertensive drugs. Issue 6071 (14th May 1977) - Goldberg, A D; Raftery, E B; Wilkinson, P
Abstract : The immediate effects on heart rate and blood pressure of withdrawing antihypertensive drugs were studied over three-day periods in 26 patients. Four groups of drugs were studied. After withdrawal all patients taking clonidine showed a considerable increase in heart rate and blood pressure with intense ectopic activity. Patients taking postganglionic neurone-blocking drugs showed a similar but less pronounced reaction with increased ventricular ectopic activity. No alarming reactions were seen after withdrawal of methyldopa or beta-blocking drugs. Methyldopa and, especially, beta-blocking drugs are less likely to produce withdrawal reactions than clonidine or the postganglionic neurone-blocking drugs, and patients taking these drugs are therefore less likely to suffer violent reactions if they forget to take their tablets.